Pengaruh Pengetahuan Akuntansi, Motivasi dan Lingkungan Keluarga Terhadap Minat Berwirausaha: Studi Kasus Mahasiswa Program Studi Akuntansi Universitas Cokroaminoto Yogyakarta - Kusuma, Jaya Hadi; Ayudiati, Citra (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to determine the influence of accounting knowledge, motivationand family environment on entrepreneurial interest among students of Cokroaminoto University Yogyakarta. The research approach used in this studyisquantitative research using the Smart-PLS application. The researchwasconducted on students of the Accounting Study Program, Faculty of Economics, Cokroaminoto University, Yogyakarta. This study uses primary data obtainedfrom the distribution of questionnaires through Google Forms. The number of respondents in this study was 79 students. The results of this study showthat thereis no influence of accounting knowledge on entrepreneurial interest, motivationhas a significant effect on entrepreneurial interest and family environment has asignificant effect on entrepreneurial interest.